Microstructure formation and evolution mechanism of Cu-Ti coating during dual-magnetron sputtering and thermo plasma nitriding. (December 2016) - Zhu, Y.D.; Yan, M.F.; Zhang, Y.X.; Chen, H.T.; Yang, Y.
Abstract: Dual magnetron sputtering and thermo plasma nitriding were performed to fabricate Cu-Ti-N coating on the surface of Cu substrate, and the microstructure formation and evolution mechanism were investigated. The results showed that the composition of the Cu-Ti coating could be tuned to be around Cu:Ti = 1:1.2 by the appropriate choice of sputtering power for the dual targets, and only amorphous Cu-Ti phases formed. During the thermo plasma nitriding process, crystalline CuTi and Cu3 Ti occurred. Moreover, a nitride layer of about 0.3 μm containing nanocrystalline TiN formed on the surface, and the multi-phase coating developed to be about 4 μm, which could provide better support for the nitrided layer. Highlights: Amorphous Cu-Ti coating with tuned Cu/Ti = 1:1.2 was fabricated by dual magnetron sputtering. Crystallization of Cu-Ti intermetallics occurred during thermo plasma nitriding. Nanocrystalline TiN formed in the outmost layer. A multiphase layer containing hard nitrides, brittle CuTi, ductile Cu3 Ti and CuTi2 was successfully fabricated.